Prevalence of HIV and syphilis co-infection and associated factors among non-commercial men who have sex with men attending a sexually transmitted disease clinic in Shenzhen, China. Issue 1 (December 2017) - Dai, Wenjie; Luo, Zhenzhou; Xu, Ruiwei; Zhao, Guanglu; Tu, Dan; Yang, Lin; Wang, Feng; Cai, Yumao; Lan, Lina; Hong, Fuchang; Yang, Tubao; Feng, Tiejian
Abstract Background Although HIV and syphilis co-infection has been frequently observed in men who have sex with men (MSM), only few studies have focused on it. Different subgroups of MSM might exhibit heterogeneous HIV and syphilis risk profiles, indicating that interventions for HIV and HIV-related co-infections may vary with different subgroups of MSM. However, no previous study has investigated HIV and syphilis co-infection among non-commercial MSM (ncMSM) attending a sexually transmitted disease (STD) clinic. Therefore, this study aimed to explore the prevalence of HIV and syphilis co-infection and associated factors among ncMSM attending an STD clinic in Shenzhen, China. Methods NcMSM attending the STD clinic of Shenzhen Center for Chronic Disease Control were recruited in this cross-sectional study every Monday between March 2013 and August 2015 using a site based convenience sampling method. An anonymous questionnaire was used to collect data regarding socio-demographic characteristics, risky sexual behaviors and HIV-related knowledge. Blood samples were collected to perform HIV and syphilis tests. Results Totally 533 participants were enrolled in this study and the prevalence of HIV and syphilis co-infection among them was 13.13%. Multivariable analyses indicated that having lived in Shenzhen for less than one year (aOR = 2.80, 95% CI = 1.30–6.05), having first anal sexual intercourse before the age of 18 (aOR = 2.78, 95% CI = 1.29–5.89), having 3 to 5 anal sexual partners in the past six months (aOR = 2.54, 95% CI = 1.19–5.40), playing exclusively receptive (aOR = 6.87, 95% CI = 3.02–15.61) or both insertive and receptive (aOR = 3.65, 95% CI = 1.64–8.09) roles in anal sexual intercourse and not always using condom in anal sexual intercourse (aOR = 2.13, 95% CI = 1.08–4.19) were associated risk factors for HIV and syphilis co-infection, relative to the non-infected ncMSM. Compared with the mono-infected ncMSM, associated risk factors for the co-infection were being unmarried (aOR = 2.47, 95% CI = 1.03–5.89) and playing exclusively receptive role (aOR = 2.44, 95% CI = 1.04–5.73) in anal sexual intercourse. Conclusions HIV and syphilis co-infection is quite prevalent among the study participants in Shenzhen. Integrated and intensified intervention strategies, specifically targeting at the non-infected and mono-infected ncMSM attending the STD clinic, are needed to reduce HIV and syphilis co-infection. Most importantly, non-infected and mono-infected ncMSM attending the STD clinic with the aforementioned associated risk factors should be given special concern.